Constitutional Labour Rights in the Gig Economy: Digital Platform Workers and Section 2(d) of the Charter - Bakan, Joel; Choudhry, Sujit (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2025)
Gig work is not new, but the introduction of digital platforms to broker its delivery vastly expands its domain. Workers can experience vulnerability in their relationships with these platforms, especially when power imbalances are acute. Collective bargaining is one way platform workers might protect themselves. However, due to their uncertain status as “employees,” platform workers are likely excluded from some, if not most, statutory collective bargaining regimes in Canada. A section 2(d) Charter right to bargain collectively could protect them from such exclusion. While early section 2(d) decisions rejected a Charter right to bargain collectively, more recent ones affirm that section 2(d) protects that right, especially for workers who experience workplace vulnerability. Many platform workers fall within that category and should therefore be entitled to Charter protection. A Charter right to bargain collectively would compel governments to act, and not act, in ways favourable to protecting those workers’ collective voice and interests.